KAJIAN AYAT-AYAT TEOLOGIS DALAM TAFSIR AL IBRIZ KARYA KH. BISRI MUSTOFA - Lailatul Mu’jizat (STIQ al-Lathifiyyah Palembang, 2019)
This article aims to discuss the interpretation of a few Qur’anic verses of Tafsir Al Ibriz, written by KH Bisri Mustofa, that contain theological teachings. From literature study it was known that KH Bisri Mustafa used bi al-ra’yi approach, as well as bi al-ma’tsur, i.e. using hadith to strengthen the intepretation of the verse. His theology is influenced by Maturidiah and Mu’tazilah, with a tasawuf style. While in terms of method, he used ijmali which tend to be short in explaining the meaning of the verse.